2019
DOI: 10.1002/jcp.28899
|View full text |Cite
|
Sign up to set email alerts
|

MiR‐199a‐3p inhibition facilitates cardiomyocyte differentiation of embryonic stem cell through promotion of MEF2C

Abstract: MicroRNAs (miRNAs) is a small molecule (19-25 nucleotide) noncoding RNA that inhibits the expression of target messenger RNA (mRNA) at the posttranscriptional level as an endogenous regulator. There is an increasing evidence that miR-199a-3p has a significant effect on the development of multiple tumors. However, the specific roles of miR-199a-3p in myocardial differentiation of embryonic stem cell still need to be investigated. Method of the hanging drop was used to build the model of cardiomyocyte differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 37 publications
(42 reference statements)
0
13
0
Order By: Relevance
“…MiR-199a-3p, same as other microRNAs, engages a broad series of mRNA targets, including numerous survival factors and cell cycle regulatory proteins to take effects [ 36 , 37 ]. Thus, the potential promotion of the regenerative response by the miR-199a-3p involves the actions of protein targets that participate in cellular senescence [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…MiR-199a-3p, same as other microRNAs, engages a broad series of mRNA targets, including numerous survival factors and cell cycle regulatory proteins to take effects [ 36 , 37 ]. Thus, the potential promotion of the regenerative response by the miR-199a-3p involves the actions of protein targets that participate in cellular senescence [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the above bioinformatics analyses suggested MEF2C owned an over 0.6 correlation coefficient with both PECAM1 and CXCR4. As a subtype of the MEF2 protein family which are expressed in a variety of tissues, MEF2C was reported to play a crucial role in myocardiogenesis (Chen et al, 2019). Intriguingly, this transcription factor has been reported to be specifically activated by the MAP kinase p38 during inflammation (Han et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…a previous study highlighted the fact that mir-199a-3p plays a crucial role during adipocyte differentiation in ovariectomized mice (21). in addition, chen et al (22) revealed that mir-199a-3p participates in the inhibition of cardiomyocyte differentiation in stem cells via the MeF2c pathway. recently, Wu et al (23) found that mir-199a-3p expression was increased in ovariectomized mice and that the upregulation of mir-199a-3p inhibited the osteogenic differentiation of BMScs in vitro.…”
Section: Mechanisms By Which Ncrnas Regulate Bmscs In Osteoporosismentioning
confidence: 95%